INCREASING THE EFFICIENCY OF MEMBRANE TECHNOLOGIES IN WATER TREATMENT PROCESSES - Mikhailovna, Kuvardina Elena (Journal of Applied Engineering Science, 2021)
The twenty-first century is the century of the rapid development of nanotechnologies, which determine the successful dynamics of the country's economy, save energy resources, and ensure a safe ecological level of the environment. Membrane processes have rightfully occupied their niche in various areas of a number of industries. Modern technologies have made it possible to create a wide range of membranes with good mechanical, thermal and chemical properties. The range of membrane devices and installations is also diverse, which are more and more improved from year to year. Water treatment of boiler houses is a necessary process that ensures successful commissioning of technological equipment of industrial enterprises, as well as heating systems. Water treatment systems are high-cost technologies, and these costs increase annually due to annually increasing trends: an increase in tariffs for water use, deterioration of water quality indicators in sources suitable for industrial use, stricter standards for quantitative and qualitative indicators for discharged effluents, increasing quality requirements treated water used in the technological cycle.
Keywords: membrane technologies; vibration; water conditioning; reagents; ultrafiltration; selectiveness of membranes